Cytotoxic Activity of 2- iminoethyl 2-(2-(1-hydroxypentan-2-yl) phenyl) Acetate from Sterculia Quadrifida R.Br Ethyl Acetate Fraction - Rollando Rollando (Journal of Global Pharma Technology, 2018)
Faloak (Sterculia quadrifida R.Br) was used empirically as a traditional medicinal plant. The information of the active compounds contained in the faloak bark was not specifically published. This study aims to determine the active compounds contained in the fraction of ethyl acetate of faloak bark which has cytotoxic effect on breast cancer cell type T47D. Extraction method use maceration, isolation compound using gradient isolation method, structural elucidation using information from IR, H-NMR, C-NMR and LC-MS. Cytotoxic activity test on breast cancer cell line T47D using MTT method. The result show the isolate compound was 2-iminoethyl 2- (1-hydroxypentan-2-yl) phenyl) acetate with IC50 value on T47D breast cancer cell 7, 12 μg/mL and with selectivity index value was 47, 53.Keywords: Sterculia quadrifida R.Br, 2-iminoethyl 2-(2-(1-hydroxypentan-2-yl) phenyl) acetate, T47D.